Let m be the present age of Madison and c be the present age of Chris.
Since Madison is 16 years older than Chris, the age of Madison can be expressed as,
![m=c+16\text{ ---(1)}](https://img.qammunity.org/2023/formulas/mathematics/college/4gdvn2woam9k3rx3aip3fcjuy64m4f84ik.png)
After 6 years, the age of Madison will be m+6 and the age of Chris will be c+6.
Since it is given that Madison will be double Chris’s age in 6 years, we can write
![m+6=2(c+6)\text{ ---(2)}](https://img.qammunity.org/2023/formulas/mathematics/college/8v70p0ogn9e6g5x43z2avqmmqhz31zgk6s.png)
Plug in equation (1) in equation (2) and solve.
![\begin{gathered} c+16+6=2(c+6) \\ c+22=2c+2*6 \\ c+22=2c+12 \\ c-2c=12-22 \\ -c=-10 \\ c=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r0v9qnecu1ddt4xjpvi4o19t76msc9mqrm.png)
Substitute c=10 in equation (1) to find m.
![\begin{gathered} m=10+16 \\ m=26 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r7pfx13lwy1in208h2qglil6suc98n1im6.png)
Therefore, the present age of Madison is 26 years and the age of Chris is 10 years.